Trajetórias educacionais e profissionais de egressos do curso técnico em guia de turismo do Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul - Campus Restinga (Porto Alegre, RS, Brasil) - Nunes, Mirelle Barcos (2018)
This thesis presents results of an investigation whose main theme is the educational and professional trajectories of graduates of the Technical Course in Tourism Guide of the Federal Institute of Education, Science and Technology of Rio Grande do Sul - IFRS, Campus Restinga, in the period of 2011-2015. This Institute composes the Centenary Federal Network of Professional, Scientific and Technological Education that for ten years has undergone an expansion process. This restructuring has made it possible to expand the offer of courses at different levels, from high school to postgraduate, democratizing the access for citizens of different socioeconomic situations, serving all the federal states of the country. In this institutional context, the Technical Course in Guide of Tourism forms professionals able to lead people in sightseeing tours in the Regional, National and South America scopes, according to the curriculum. Historically offered in the private educational network, with the expansion of the Federal Network, the formation of Tourism Guides became accessible to citizens who until then were at the margin of opportunities in this area of education. This Course synthesizes this history, because the community of the Restinga neighborhood, where the IFRS is located, carries the marks of social exclusion of a periphery in the midst of a metropolis. Thus, leisure practices and tourist experiences of many graduates of this Course were only possible through the Technical Course in Tourism Guide. In this way, this course has different meanings in the educational and professional trajectory of these graduates. The study was based on the Field Theory of Pierre Bourdieu, especially from the deepening of central concepts of this theory, such as field, trajectory, cultural capital, strategy and habitus. Methodologically classified as quantitative and qualitative research, this work sought to identify the effects of the passage through said course and the presence of an educational institution focused on technical and technological training in the daily life of a periphery. Data were collected from the analysis of institutional documents and an interview with the server responsible for the implantation of the Campus Restinga, a questionnaire answered by 34 graduates of the Course in the respective period and from narrative interviews with ten of these subjects. The study made possible an analysis of the educational and professional trajectories of graduates in order to visualize the transformations that occurred in these trajectories, from the passage through the technical training in question, considering the context of the changes in the political scope of the offer of Professional Education in the Country. The results show upward trajectories in relation to the intergenerational schooling of the family groups, as well as amplification of the modes of acquisition of incorporated cultural capital. In this sense, expressions of enthusiasm and confidence about the path taken, the investments in the career, and the plans for the future, reveal that the Federal Institute Campus Restinga was an important ally for these changes in the trajectories of the graduates. At the same time, it signaled and invited to the confrontation, but also offered the support necessary for the graduates to succeed in the face of the old and entrenched educational and labor difficulties imposed by an unequal and exclusive system. Thus, this alliance translates the relevance of the democratizing public policies of access to educational rights, at all levels and in different social spaces.